Taxonomy and Distribution of Benthic Foraminifera from the Sediment of Palk Strait South East Coast of India - Thilagavathi, B (International Journal of Pharmaceutical & Biological Archive, 2012)
Taxonomy and Distribution of Benthic Foraminifera from the Sediment of Palk Strait South East Coast of India